2023
DOI: 10.3390/s23094506
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Shooting Events in Soccer Videos Using Complete Bipartite Graphs and Players’ Spatial-Temporal Relations

Abstract: In soccer, quantitatively evaluating the performance of players and teams is essential to improve tactical coaching and players’ decision-making abilities. To achieve this, some methods use predicted probabilities of shoot event occurrences to quantify player performances, but conventional shoot prediction models have not performed well and have failed to consider the reliability of the event probability. This paper proposes a novel method that effectively utilizes players’ spatio-temporal relations and predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Thus, the BNN enables more reliable predictions than conventional methods based on deterministic machine learning. Note that we have previously presented the preliminary results in previous studies [38][39][40][41], where we demonstrated the effectiveness of incorporating visual information and players' distances into graphs to achieve shot prediction from soccer videos.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…Thus, the BNN enables more reliable predictions than conventional methods based on deterministic machine learning. Note that we have previously presented the preliminary results in previous studies [38][39][40][41], where we demonstrated the effectiveness of incorporating visual information and players' distances into graphs to achieve shot prediction from soccer videos.…”
Section: Introductionmentioning
confidence: 74%
“…Finally, we predict the probability of the shot occurrence as well as output the prediction uncertainty based on the BNN. A part of this figure is sourced from our previous paper [39].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The broader scope of strategy modelling in football has previously been addressed from various individual angles, such as pass prediction 14 – 16 , shot prediction 3 or corner kick tactical classification 7 . However, to the best of our knowledge, our work stands out by combining and evaluating predictive and generative modelling of corner kicks for tactic development.…”
Section: Resultsmentioning
confidence: 99%
“…Several recent methods attempt to improve tactical coaching and player decision-making through artificial intelligence (AI) tools, using a wide variety of data types from videos to tracking sensors and applying diverse algorithms ranging from simple logistic regression to elaborate neural network architectures. Such methods have been employed to help predict shot events from videos 3 , forecast off-screen movement from spatio-temporal data 4 , determine whether a match is in-play or interrupted 5 , or identify player actions 6 .…”
Section: Introductionmentioning
confidence: 99%